2020
DOI: 10.1111/cas.14659
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of S100A10 in metastasized breast cancer stem cells

Abstract: Metastatic progression remains the major cause of death in human breast cancer. Cancer cells with cancer stem cell (CSC) properties drive initiation and growth of metastases at distant sites. We have previously established the breast cancer patient‐derived tumor xenograft (PDX) mouse model in which CSC marker CD44+ cancer cells formed spontaneous microscopic metastases in the liver. In this PDX mouse, the expression levels of S100A10 and its family proteins were much higher in the CD44+ cancer cells metastasiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…They observed no change in tumor growth at the primary sites but did observe inhibition of metastatic capacity. Our work, therefore, was consistent with other studies showing the importance of S100A10 in breast cancer [ 177 , 193 , 194 , 195 ].…”
Section: Role Of the Anxa2/s100a10 Heterotetramer In Cancersupporting
confidence: 93%
See 1 more Smart Citation
“…They observed no change in tumor growth at the primary sites but did observe inhibition of metastatic capacity. Our work, therefore, was consistent with other studies showing the importance of S100A10 in breast cancer [ 177 , 193 , 194 , 195 ].…”
Section: Role Of the Anxa2/s100a10 Heterotetramer In Cancersupporting
confidence: 93%
“…After several months the orthotopic tumors and the metastases in the lung tissues are analyzed. These investigators observed that S100A10 was one of the most highly upregulated proteins in the metastasized cancer cells compared to the tumor cancer cells [ 193 ]. These researchers then performed constitutive knockdown of S100A10 in MDA-MB-231 cells followed by orthotopic transplantation in the mammary fat.…”
Section: Role Of the Anxa2/s100a10 Heterotetramer In Cancermentioning
confidence: 99%
“…Moreover, overexpression of p11 in human breast cancer cell line MDA MB 231 resulted in increased organoid-forming, invasive, and metastatic capacity, whereas loss of p11 resulted in a reduced number of organoids. Interestingly, these studies also established that p11 upregulated stem cellrelated genes, such as OCT4, SOX2, and NANOG, in the organoids, suggesting a novel function of p11 in promoting metastasis of CSC [211]. Lu et al, observed that chemotherapy (paclitaxel or carboplatin)-induced p11 is mediated by HIF-1, which further promotes epigenetic modulation and transcriptional activation and expression of pluripotency factors, such as NANOG, SOX2 and KLF4, in breast cancer cell lines.…”
Section: Involvement Of P11 In Biological Processes and Cancermentioning
confidence: 95%
“…It was clarified that smoothened (Smo) up-regulated the level of STAT3, accordingly promoting BCSCs maintenancerelated liver metastasis in BC [61]. Besides, S100A10 was discovered to participate in enhancing BCSCs maintenance-related liver metastasis [62]. In addition, combined treatment with JAK2 inhibitors (ruxolitinib and pacritinib) and SMO inhibitors (vismodegib and sonidegib) could served as a suppressor in BCSCs maintenance-related liver metastasis by simultaneously blocking JAK2-STAT3 and SMO-GLI1/tGLI1 signaling pathways [63].…”
Section: Bcscs-related Liver Metastasismentioning
confidence: 99%